Arterial stiffness and dementia pathology: Atherosclerosis Risk in Communities (ARIC)-PET Study. (3rd April 2018) - Hughes, Timothy M.; Wagenknecht, Lynne E.; Craft, Suzanne; Mintz, Akiva; Heiss, Gerardo; Palta, Priya; Wong, Dean; Zhou, Yun; Knopman, David; Mosley, Thomas H.; Gottesman, Rebecca F.
Abstract : Objective: Arterial stiffness has been associated with evidence of cerebral small vessel disease (cSVD) and fibrillar β-amyloid (Aβ) deposition in the brain. These complex relationships have not been examined in racially and cognitively diverse cohorts. Methods: The Atherosclerosis Risk in Communities (ARIC)–Neurocognitive Study collected detailed cognitive testing for adjudication of dementia and mild cognitive impairment (MCI), brain MRI, and arterial stiffness by pulse wave velocity (PWV, carotid-femoral [cfPWV] and heart-carotid [hcPWV]). The ARIC-PET ancillary study added Aβ imaging using florbetapir ([ 18 F]-AV-45) to obtain standardized uptake volume ratios and defined global Aβ-positivity as standardized uptake volume ratio >1.2. One-SD increase in PWV was related to brain volume, MRI-defined cSVD (e.g., cerebral microbleeds and white matter hyperintensity), and cortical Aβ deposition adjusted for age, body mass index, sex, race, and APOE ε4 status. We examined the cross-sectional relationships including interactions by race, APOE ε4 status, and cognition. Results: Among the 320 ARIC-PET participants (76 [5] years, 45% black, 27% MCI), greater central stiffness (hcPWV) was associated with greater Aβ deposition (odds ratio [OR] = 1.31, 95% confidence interval [CI] 1.01–1.71). Greater central stiffness (cfPWV) was significantly associated with having lower brain volumes in Alzheimer disease–susceptible regions (in mm 3, β = −1.5 [0.7 SD], p = 0.03) and high white matter hyperintensity burden (OR = 1.6, 95% CI 1.2–2.1). Furthermore, cfPWV was associated with a higher odds of concomitant high white matter hyperintensity and Aβ-positive scans (OR = 1.4, 95% CI 1.1–2.1). These associations were strongest among individuals with MCI and did not differ by race or APOE ε4 status. Conclusions: Arterial stiffness, measured by PWV, is an emerging risk factor for dementia through its repeated relationships with cognition, cSVD, and Aβ deposition.